2020
DOI: 10.1200/jco.19.03296
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Plus Nivolumab in Patients With Advanced Gastric or Colorectal Cancer: An Open-Label, Dose-Escalation, and Dose-Expansion Phase Ib Trial (REGONIVO, EPOC1603)

Abstract: PURPOSE This is a phase Ib trial of regorafenib plus nivolumab for gastric and colorectal cancer. PATIENTS AND METHODS Enrolled patients received regorafenib plus nivolumab in a dose-finding part to estimate the maximum tolerated dose. Additional patients were enrolled in a dose-expansion part. Regorafenib of 80-160 mg was administered once daily for 21 days on/7 days off with nivolumab 3 mg/kg every 2 weeks. The primary end point was dose-limiting toxicity (DLT) during the first 4 weeks to estimate the recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
415
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(476 citation statements)
references
References 26 publications
23
415
3
1
Order By: Relevance
“…The counterparts in the TCGA cohort are shown in (online supplemental figure 6SF-H). As recently the combination of regorafenib plus nivolumab has shown a manageable safety profile and encouraging antitumor activity in colon cancer, 37 we further investigated the association of the MSRS and VEGF activities in MSS, MSI-L, and MSI-H tumors. The results indicated a strikingly higher association of the MSRS and VEGF in MSI-H tumors (0.53) than in MSI-L tumors (0.34) and MSS tumors (0.14) ( figure 7D).…”
Section: Association Between Microsatellite Status and Gene Mutationsmentioning
confidence: 99%
“…The counterparts in the TCGA cohort are shown in (online supplemental figure 6SF-H). As recently the combination of regorafenib plus nivolumab has shown a manageable safety profile and encouraging antitumor activity in colon cancer, 37 we further investigated the association of the MSRS and VEGF activities in MSS, MSI-L, and MSI-H tumors. The results indicated a strikingly higher association of the MSRS and VEGF in MSI-H tumors (0.53) than in MSI-L tumors (0.34) and MSS tumors (0.14) ( figure 7D).…”
Section: Association Between Microsatellite Status and Gene Mutationsmentioning
confidence: 99%
“…No responses were detected in a cohort of pMMR mCRC treated with compassionate administration of nivolumab or pembrolizumab in combination with regorafenib in a single United States (U.S.) center. Among five patients (31%) who experienced stable disease as best response, four had no liver metastases [28]. In line with REGONIVO, this finding could suggest that patients with liver metastases are characterized by a lower antitumor immune response and may be less likely to benefit from checkpoint inhibition [121].…”
Section: Anti-tams + Immune Checkpoint Inhibitorsmentioning
confidence: 57%
“…[4] In CRC, EPOC1603 clinical trial of regorafenib plus nivolumab therapy showed promising effect with an ORR of 36% in treatmentrefractory CRC, but relatively unsatisfactory outcomes in the subgroup of patients with liver metastases. [18] Meanwhile, phase IIIb CONSIGN study showed that regorafenib signi cantly improved survival in treatment-refractory CRC, but liver metastases was a signi cant adverse factor in the progression-free survival (PFS) of regorafenib for metastatic CRC. [19] The poor outcome of patients with liver metastases suggested a possibly distinct microenvironment in liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Unfortunately, in patients with liver metastases, the e cacy of regorafenib monotherapy or its combination with immunotherapy was undesirable. [18,19] Previous studies have found the heterogeneity of lymphocyte type, lymphocyte number, KRAS status between primary tumors and liver metastases of colorectal cancer, which suggested that there may be different in the microenvironment between primary tumors and liver metastases. [20,21] The current study aim to explore the status of the PD-L1 expression difference between in primary tumors and in liver metastases of CRC to nd those in uence factors to evaluate the PD-L1 expression status accurately.…”
Section: Introductionmentioning
confidence: 99%